Model Perlindungan Hukum Terhadap Perempuan dan Anak Korban Tindak Pidana Kekerasan Melalui Pedoman Kejaksaan No. 1 Tahun 2021 tentang Akses Keadilan Bagi Perempuan dan Anak dalam Penanganan Perkara Pidana - Zurnetti, Aria; Mulyati, Nani; Nova, Efren; Afrizal, Riki (Nagari Law Review, 2024)
Prosecutor's Guidelines Number 1 of 2021, concerning Providing Access to Justice for Women and Children Involved in Criminal Proceedings, is significant progress in strengthening legal protection for victims of violence, especially in the West Sumatra Province, Indonesia, where law enforcement officers are concentrated. In the past, criminal procedural law seemed to primarily regulate the safeguarding of the rights of offenders, as mandated by Law Number 8 of 1981 regarding Criminal Procedure. In contrast, recent legal developments and breakthroughs, exemplified by this Guide, indicate a significant shift in focus toward protecting victims and witnesses, thereby overcoming the phenomenon of victimization. This article discusses problems in investigations carried out in the jurisdiction of Padang, Bukittinggi, Payakumbuh, Batusangkar, Pesisir Selatan, Pasaman, and Pariaman District Attorneys. Initially, an overview of the circumstances surrounding the issuance of Guideline No. 1 of 2021; then a study will be carried out on the application of the principles of protection of children and women in the prosecution process throughout the region; and finally, the development of legal protection models to ensure that children and women victims of violent crimes have access to justice. The research method used is sociological, legal research with a descriptive approach, utilizing primary and secondary data. This research finds an effective model of legal protection for women and children victims of violent crimes so that they can access justice in the criminal legal process. Therefore, it is recommended that law enforcement agencies have a deeper understanding of legal protection for victims of violence and contribute to increasing access to justice for women and children in criminal cases in the jurisdiction of the West Sumatra High Prosecutor's Office.